Pelapor Kecurangan: Persepsi Kerugian Personal, Status Pelanggar, Dukungan dan Perlindungan Organisasi - Setiany, Erna; Zamzami, Annisa Hakim; Agustiningsih, Sri Wahyu (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2020)
Employee participation as a whistleblower is still low. This is due to various factors that make employees reluctant to report the fraud they have encountered, such as perceptions of personal loss and the status of offenders. On the other hand, there are factors that allow employees to blow the whistle, such as organizational support and protection. Thus, this study examines personal cost factors, offender status, organizational support and protection against internal whistleblowing intentions. Respondents of this study were 112 accounting students who have worked in both the private and government sectors in DKI Jakarta. The results showed that only organizational protection had a significant effect on internal whistleblowing intentions. Meanwhile, personal costs, violator status, and organizational support have no significant effect on internal whistleblowing intentions.Partisipasi karyawan menjadi whistleblower masih tergolong rendah. Hal ini disebabkan oleh berbagai faktor yang membuat karyawan enggan untuk melaporkan kecurangan mereka temui, seperti persepsi kerugian pribadi dan status pelanggar. Dilain sisi terdapat factor yang memungkinkan karyawan untuk melaporkan kecurangan, seperti dukungan dan proteksi organisasi. Dengan demikian penelitian ini menguji faktor persepsi kerugian pribadi, status pelanggar, dukungan dan proteksi organisasi terhadap niat pelaporan kecurangan internal. Responden penelitian ini adalah 112 mahasiswa akuntansi yang sudah bekerja baik sektor swasta maupun pemerintahan di DKI Jakarta menggunakan kuisioner dan dianalisis menggunakan SEM berbasis kovarian dengan Smart PLS 2.0. Hasil penelitian menunjukkan bahwa hanya perlindungan organisasi yang signifikan berpengaruh terhadap niat pelaporan kecurangan internal. Sedangkan spersepsi kerugian pribadi, status pelanggar, dan dukungan organisasi tidak signifikan berpengaruh terhadap niat pelaporan kecurangan internal.